High‐Resolution Seismic Imaging of Fault‐Controlled Basins: A Case Study From the 2009 Mw 6.1 Central Italy Earthquake. Issue 4 (5th April 2022) - Bruno, Pier Paolo G.; Villani, Fabio; Improta, Luigi
Abstract: We present the first seismic reflection images of the Paganica and Bazzano basins, two tectonic basins developed in the hanging wall of the Paganica‐San Demetrio Fault System, the causative fault of the 2009 Mw 6.1 L'Aquila earthquake, Italy. Five high‐resolution seismic profiles were acquired along a main, 7 km long transect cutting across the strands of an active fault system in urbanized areas with widespread sources of seismic noise. Three processing approaches were chosen to tackle a variable and site‐dependent data quality . To aid interpretation of this complex setting, we complemented seismic amplitude images with energy and similarity attributes as well with post‐stack acoustic impedance inversion. The final seismic sections expose, with unprecedented resolution, the basins' structure and the uppermost splays of the 2009 earthquake. The seismic data show fine details of the subsurface stratigraphic setting, revealing continental depocenters carved in the marine Meso‐Cenozoic substratum and displaced by a series of conjugate normal faults, mostly unknown before this study. Several of the imaged fault strands connect to the 2009 coseismic surface ruptures. Matching the seismic interpretation with constraints from surface geology and shallow boreholes, published data from field surveys and scientific drilling, we present a structural map of the Bazzano and Paganica basins with an estimation of the depth of the Meso‐Cenozoic substratum. This map highlights a different structure, evolution, and age of the two basins, with the older Bazzano basin that likely began to form in late Pliocene. Key Points: Five high‐resolution seismic profiles image the shallow architecture of the 6 April 2009 (Mw 6.1) L'Aquila earthquake fault hanging wall The final images expose the structure of Paganica and Bazzano basins and seismogenic faults dissecting them with unprecedented resolution Interpretation of seismic data suggests that Paganica and Bazzano basins have different age, structure, and evolution